Problems of Reliable and Timely Delivery of Information on the Servers - Dadamuxamedov Alimjon (Genius Journals, 2023)
The article analyzes the advantages and disadvantages of reliable and timely delivery of information to the servers of religious educational institutions. Religious educational institutions are a special type of organization that requires reliable and timely delivery of information to their servers. This article discusses the main directions of ensuring the reliability and timely delivery of information to servers.
Keywords: network protocols; multipath redundant transmissions; delivery time limits